Cointegration and Causality Analysis on Developed Asian Markets for Risk Management and Portfolio Selection - Herwany, Aldrin; Febrian, Erie (Gadjah Mada International Journal of Business, 2008)
Both practitioners and academics demand a linkage model across financial markets, particularly among regional capital markets, for both risk management and portfolio selection purposes. Researchers frequently use cointegration and causality analysis in investigating the dependence or co-movement of three or more stock markets in different countries. However, they mostly conduct causality in mean tests but not causality in variance tests.This study assesses the cointegration and causal relations among seven developed Asian markets, i.e., Tokyo, Hong Kong, Korea, Taiwan, Shanghai, Singapore, and Kuala Lumpur stock exchanges, using more frequent time series data. It employs the recently developed techniques for investigating unit roots, cointegration, time-varying volatility, and causality in variance. For estimating portfolio market risk, this study employs Value-at-Risk with delta normal approach. The results would recommend whether fund managers are able to diversify their portfolio in these developed stock markets either in long run or in short run.